2020
DOI: 10.1177/1045389x20924822
|View full text |Cite
|
Sign up to set email alerts
|

Strain-based health indicators for the structural health monitoring of stiffened composite panels

Abstract: A common defect of composite-stiffened structures is the disbond at the interface between the two constituents (skin/stringer), as a result of inefficient manufacturing process or foreign object impacts in service. Generally, discontinuities within the volume of an elastic solid medium, subjected to mechanical load, cause anomalies on the strain field in the near vicinity of the discontinuity. Utilizing this observation, this work investigates the effect of artificially induced disbonds in the skin/stiffener i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…Several HIs for both constant and variable amplitude fatigue were developed and their performance was presented throughout fatigue tests. The strain-based HIs, i.e., HI 1 and HI 2 , were used in [7] to successfully detect damage in quasi-static numerical tests. The HIs investigated in the present work are intended for diagnostic and prognostics tasks in which monotonic trends are highly desirable; hence, the proposal of the fused HIs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several HIs for both constant and variable amplitude fatigue were developed and their performance was presented throughout fatigue tests. The strain-based HIs, i.e., HI 1 and HI 2 , were used in [7] to successfully detect damage in quasi-static numerical tests. The HIs investigated in the present work are intended for diagnostic and prognostics tasks in which monotonic trends are highly desirable; hence, the proposal of the fused HIs.…”
Section: Discussionmentioning
confidence: 99%
“…Even looking at the same sensor on two different specimens, it is not guaranteed that the behavior will be similar because the buckling modes may also affect the local behavior. However, this HI can provide useful information regarding the damage progression, as seen in [7], by successfully monitoring disbond growth. It is worth pointing out that HI 2 curves start to diverge when damage becomes significant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The active thermometry, which operates in such a way that a heat pulse is introduced and the temperature response is measured simultaneously, is effective in determining thermal properties such as thermal resistivity, thermal diffusivity, specific heat, and soil water content (Bristow, 1998;Freifeld et al, 2008;Krishnaiah et al, 2004). On the other hand, distributed fiber optic sensing (DFOS) techniques have been widely employed for structural health monitoring of various structures due to their unique advantages, such as small profile, flexible shape, high sensitivity, immunity to electromagnetic interference, distributed and long distance monitoring capability (Fan et al, 2019;Gu¨emes et al, 2010;Li et al, 2004;Li and Wu, 2007;Milanoski and Loutas, 2020;Villalba and Casas, 2013;Yeager et al, 2018). It has been demonstrated that the active thermometry, when instrumented with the distributed fiber optic temperature sensing techniques, presents promising application capability in the field of SHM, such scour monitoring and free span detection of subsea pipeline (Zhao et al, 2012(Zhao et al, , 2013a(Zhao et al, , 2013b(Zhao et al, , 2015, rebar corrosion detection in reinforced concrete (Li et al, 2016), and liquid level monitoring of producing oil wells (Peng et al, 2014).…”
Section: Introductionmentioning
confidence: 99%